HUBUNGAN ANTARA KEDISIPLINAN DENGAN HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN PKN DI SD INPRES 51 KABUPATEN SORONG - Michael Rizard Tahitu; Syam Kusumaningrum; Muhammad Faizin (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This research aims to determine whether or not there is a relationship between discipline and student learning outcomes in Civics subjects in class IV SD Inpres 51 Sorong Regency. Meanwhile, the theoretical benefit of this research is that it proves that there is a relationship between discipline and student learning outcomes in Civics subjects in class IV of SD Inpres 51, Sorong Regency. The research objects in this study were fourth grade students at SD Inpres 51 Sorong Regency. Data collection techniques use questionnaires and tests. The validity test of the instrument uses the Pearson product moment (r) correlation formula and the reliability test uses the Spearman Brown formula. In the results of the regression analysis, several data tests were carried out, namely: normality test, linearity test, and regression equation. Testing the research hypothesis uses a simple regression formula and the significance of simple regression and the t test. The results obtained based on the regression equation analysis test are the X value for Discipline of (29.714) and the Y value for learning outcomes of (0.501) with a Sig. count = 0.329 > 0.05. The regression coefficient figure is 0.501, this figure means that for every 1% increase in the level of discipline (X), student learning outcomes (Y) will increase by 0.501. Because the regression coefficient value is minus (+), it can be concluded that there is a relationship between discipline (X) and learning outcomes (Y), so the regression equation is Y = 29.714 + 0.501. This means that the Ha hypothesis is accepted, it can be concluded that there is a relationship between discipline and the learning outcomes of Class IV students in Civics subjects at SD Inpres 51, Sorong Regency.